First taxon date and stable isotopes (d13C, d15N) for the large hypercarnivorous South American canid Protocyon troglodytes (Canidae, Carnivora) - Prevosti, Francisco Juan (2013)
Protocyon troglodytes was a hypercarnivorous South American canid that died out during the Late Pleistocene-early Holocene extinction, an event that eliminated most large mammals on the continent. The precise timing of these extinctions is poorly understood in South America, primarily due to a lack of radiometric dates on taxa. Of the extinct South American canids, P. troglodytes have the most extensive fossil record and widest distribution. However, the age of these specimens is based on relatively coarse association with other dated taxa or sediments. This paper describes an unpublished specimen of P. troglodytes and present the first 14C date and stable isotopes (d13C and d15N) for the species. This is the first taxon date for the genus and species, with an age of 17,338 85 BP, and represents the youngest specimen dated by any means. The isotopes indicate that P. troglodytes was a hypercarnivore, in agreement with morphological studies, and that Equus neogeus, Hippidion principale, Stegomastodon platensis, Toxodon, and Megatherium americanum may have been part of its diet.